Improved Employee Performance at PT Alas Harum Bali - Desak Made Sukarnasih; I Putu Yoga; Desak Ayu Sriary Bhegawati (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
This research was conducted based on the research gap and differences in the focus of the discussion on knowledge sharing, individual innovation abilities, and organizational citizenship behavior on employee performance. In addition, there are also research problems regarding the decline in employee performance at PT. Alas Harum Bali can be seen from the high level of employee absenteeism. This research was conducted at PT. Alas Harum Bali with a population of 65 employees and a sample of 65 employees. All data obtained from the distribution of questionnaires that can be used, then analyzed using SPSS 25. The results of the study indicate that knowledge sharing has a positive and significant effect on employee performance, individual innovation capability has a positive and significant effect on employee performance, and organizational citizenship behavior has a positive and significant impact on employee performance. Employee performance, knowledge sharing, individual innovation ability, and organizational citizenship behavior have a positive and significant effect on employee performance. This research suggests that knowledge sharing can be increased by taking into account the existing indicators. Individual innovation ability can be progressed by paying awareness to personality characteristic indicators. Organizational citizenship behavior can be improved by paying attention to courtesy indicators. Performance can be improved by paying attention to effectiveness indicators.